A Character Formation Model in Integral Schools: An Analysis Through Weber's Theory of Social Action - Iwan Kuswandi; Asmoni Asmoni (AL-ISHLAH: Jurnal Pendidikan, 2025)
Character development in education is essential for fostering moral and ethical values in students. This study examines character development models within two Islamic elementary schools—Luqman Al-Hakim Integral Elementary School and Al-Wathoniyah Integrated Islamic Elementary School—through the lens of Max Weber’s social action theory. The study explores how these schools integrate character education within their curricula. A qualitative research approach was adopted, utilizing observations, interviews, and document analysis to collect data. The qualitative analysis method was employed to interpret the findings, focusing on how character education is structured and implemented in both institutions. The findings indicate that Luqman Al-Hakim Integral Elementary School emphasizes monotheistic beliefs in character development, fostering a deep connection between religious principles and daily life. In contrast, Al-Wathoniyah Integrated Islamic Elementary School applies the water philosophy, which promotes adaptability, patience, and resilience. Both institutions actively engage parents in the educational process to reinforce character formation at home. Additionally, the curriculum integrates general education with Islamic teachings, particularly the Quran, ensuring a holistic approach to character building. The study highlights the significance of integrated character education models in Islamic schools. The incorporation of religious values alongside academic knowledge fosters well-rounded students with strong moral foundations. These findings suggest that collaborative efforts between educators and parents enhance character development, making such models effective for broader implementation in Islamic education.